Temperature effects on longevity and composition of dry-harvested Aspergillus niger spores by P. N. Singh and M. Salim. - Singh, P.N; Salim, M. (1985)
Temperature effects of longevity and composition of dry-harvested aspergillus niger spores were studied. Storage at 35 degrees greatly reduced spore rermination while no significant change was observed during storage at 25 degrees C. Sugar and organic acid concentrations of spores decreased storage at 35 degrees C. There was greater free amino acid concentration in spores at low (25 degrees C) than at high (35degrees C) temperatures. Greatest decrease occurred in the proline content.